Night shift work and osteoporosis - bone turnover markers among female blue-collar workers in Poland. (3rd June 2022) - Bukowska-Damska, Agnieszka; Skowronska-Jozwiak, Elzbieta; Kaluzny, Pawel; Lewinski, Andrzej
ABSTRACT: Osteoporosis is an important public health problem worldwide. Although many factors relating to bone structure have been described so far, the current knowledge on the occupational factors that may affect bone tissue metabolism is strongly limited. Literature data suggest that night shift work, via circadian rhythm disruption, may be considered a potential risk factor. To this date, only five epidemiological studies addressing this problem have been conducted worldwide. The outcomes of three studies confirmed such relationship, namely, a higher fracture risk was found among nurses with a long lifetime duration of night shift work in one study; and a lower bone mineral density was associated with occupational activity during night-time in two studies. In adults, the bone undergoes constant remodelling through bone resorption followed by bone formation. The various molecules released into the circulatory system during these processes are called bone turnover markers. We investigated the possible associations between night shift work and selected bone turnover markers: N-terminal propeptide of type I procollagen (P1NP), C-terminal cross-linked telopeptide of type I collagen (CTX), osteocalcin, osteopontin, fibroblast growth factor 23 (FGF-23) and osteoprotegerin, measured in plasma of 189 female blue-collar workers. A significantly higher bone turnover rate was noted among the women working night shifts than among those working only during the day. This may potentially lead to a future development of osteoporosis in this population even if the macroscopic changes in the bone structure are not detectable. Night shift work is a prevailing occupational characteristics nowadays. It has been estimated that about 15–20% of the working population in Europe and the USA perform work under this system. Thus, the problem of osteoporosis can affect a large part of the working-age population.